Comparative assessment of the antigenity of autogenic vaccine against salmonelosis in the RA and RG - O. P. Boiko; B. M. Kurtiak; T. O. Pundiak; P. K. Boiko; O. M. Sen’; M. S. Romanovyh; G. V. Sobko (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки, 2018)
The results of the comprehensive approach to the diagnosis, general and special measures for the elimination of the infection center for the outbreak of Salmonella in calves in one of the large dairy farms in the Volyn region are presented. The use of classical diagnostic methods using modern environments and approaches made it possible to isolate and identify two types of Salmonella Typhimurium and S. dublin. Antibiotic therapy of calves for salmonellosis calves was carried out with labeled antibiotics in combination with medicinal products of symptomatic nature. Forced current and final disinfection of cages and whole calf, as well as wicker yards and cows were carried out with a 0.1% solution of the new disinfection preparation “Epydes”, created on the basis of derivatives of polyhexamethylenguanidine (PGMG), at a rate of 0.3 l/m2. For a specific prevention of salmonellosis, we designed our two series of autogenic vaccines from isolated strains of salmonella, the difference between which was the choice of adsorbent. The study of the tension of humoral immunity in cats and calves vaccinated against salmonellosis in agglutination and indirect hemagglutination reactions revealed high levels of antibodies to immunogens that were part of two experimental autopsy series of autogenic vaccines. In this case, the immune response to the antigens of the Tifimurium was higher than that of Dublin antigens. Titres of antibodies from cats and calves vaccinated with a vaccine in which the aerosol was used as an adsorbent were higher than those for a vaccine in which an aluminum hydroxide was used as an adsorbent. The reaction of indirect agglutination showed several times the higher sensitivity to detect salmonella antibodies than the agglutination reaction, which is the basis for recommending it as an immunological method of tension of humoral immunity for animal salmonellosis. The comprehensive approach to diagnosis of disease, modern approaches to the treatment of calves with salmonella, the destruction of the pathogen in the environment and the modern approach to the immunization of the infection, made it possible to improve the economy throughout the year from salmonella caused by two types of salmonella.